To the means and beyond: Understanding variation in students' perceptions of teacher emotional support. (June 2018) - Schenke, Katerina; Ruzek, Erik; Lam, Arena C.; Karabenick, Stuart A.; Eccles, Jacquelynne S.
Abstract: Student perceptions of the classroom environment are used as a policy-relevant marker of teacher quality. Yet the influences on students' perceptions are less well understood. We examined (a) whether individual-level factors (achievement goals, perceptions of their previous classroom, and teacher ratings of ability) were associated with students' perceptions of teacher emotional support, and (b) whether classroom observations of teacher unfairness/unfriendliness predicted systematic within-classroom variation in students' reports of emotional support. Multilevel analysis of 1303 students in 80 7th grade mathematics classrooms indicated that students' perceptions of their 6th grade teacher, mastery orientation, and the teacher's perceptions of ability predicted end-of-the-year perceptions of emotional support. Although the observed level of teacher unsupportiveness did not predict mean-level of emotional support, students' perceptions of their teachers were more variable in classrooms observed as higher in unfairness/unfriendliness. Investigating heteroskedasticity highlights the importance of using methods for understanding variability in students' perceptions of the classroom. Highlights: Sought to understand what predicts students' perceptions of emotional support. Sample was 1303 7th grade students in 80 mathematics classrooms. Observations did not predict mean-level but predicted within-classroom variance. Mastery goals and students' previous perceptions predicted mean-level perceptions. Teacher's rating of the student also predicted mean-level perceptions.